Human Resource (HR) Management New Dynamics in Hiring, Technology Adoption, Work Environment Diversity: HR Managers’ Interviews - Christos PAPADEMETRIOU; Dimitrios BELIAS; Konstantina RAGAZOU (Communications of International Proceedings, 2024)
This paper examines the principal issues encountered by Human Resource Management (HRM) in the contemporary business landscape, driven by swift shifts in workforce expectations, technology progress, and international labor rules. This study is significant due to the developing nature of Human Resource Management, where conventional methodologies may be inadequate for contemporary situations. The study examines the evolving dynamics of recruiting, employee retention, legal adherence, technological incorporation, and the management of a diverse workforce. The study identifies significant difficulties faced by HR departments and proposes adaptive techniques through a comprehensive analysis of literature, case studies, and interviews with HR practitioners. The results underscore the necessity for Human Resource Management to adopt emerging technologies, like data analytics and artificial intelligence, to improve decision-making and operational efficiency. The study highlights that adherence to changing labor rules and promoting staff engagement in a technology-driven environment are crucial for organizational performance. This research's distinctiveness is found in its comprehensive examination of how HR professionals may strategically leverage technology and promote inclusivity to maintain competitiveness. The research offers significant insights but also recognizes its limits, especially the dependence on qualitative data, which may influence the generalizability of the results. Future research may enhance its findings by integrating quantitative methodologies to offer a more comprehensive and data-driven analysis of HRM concerns.
Keywords: HRM Practices; Recruitment; Talent Acquisition; Employee Retention; Engagement; Technology